Correlation of Serum Electrolyte Changes with Severity of Birth Asphyxia in Newborns - Najaf Masood, Sidra tul Muntiha, Muddassar Sharif , Rai Muhammad Asghar (Journal of Rawalpindi Medical College, 2016)
Background: To compare the changes in serum electrolytes in asphyxiated newborns of different severity with control group. Methods: In this case control study 150 cases were enrolled and divided into three groups of 50 cases each. Group one included asphyxiated patients with Sarnat stage II, group two included asphyxiated patients with Sarnat stage III and group three included control group with no birth asphyxia. Cases and controls were full term babies weighing 2.5kg or more. Cases included newborns with APGAR score less than 7 at 5 min of birth. Controls included newborns with APGAR score 7 or more at 5 min after the birth. Neonates with congenital anomalies, serum creatinine >1.5mg/dl, suspected metabolic diseases or infants of mothers with hypertension, diabetes mellitus, toxemia of pregnancy, mothers who received general anesthesia or drugs that cause CNS depression in newborn, mothers with history of febrile illness upto two weeks before delivery and mothers with abnormal serum electrolytes status pre and immediately post delivery were not included.Cord Blood samples of all three groups were taken within 5 minutes of birth for estimation of serum electrolyte levels (Na+, Ca++, K+). Mean values of serum electrolytes were compared by ANNOVA test and p < 0.05 was taken as significant. Results: Mean serum sodium levels were found decreased in cases of group I and II as compared to the control group (133.76+4.98 & 132.96+6.01 mEq/L Vs 139.64+2.36 mEq/L respectively p<0.05). Mean serum calcium levels were also found significantly reduced in cases of group I and II as compared to the control group (8.68+0.70 & 8.54+0.92 mg/dl Vs 9.55+0.43 mg/dl respectively p<0.05) while mean serum potassium levels were found higher in group I & II cases versus controls (4.8+0.62 &4.63 +0.35 mEq/L Vs 4.42 +0.41 mEq/L respectively p<0.05). Conclusions: Hyponatremia and hypocalcaemia showed linear correlation with severity of birth asphyxia, while serum potassium levels remained within high normal range.